Variations in the type of abrasive material used in the formulation of body scrub preparations on the evaluation of the preparation - Juvita Herdianty; Arif Wijayanto (Universitas STRADA Indonesia, 2021)
Cosmetics are products that are used to clean and beautify the skin. Body scrubs or what is commonly known as bath scrubs are scrubs that are used when the skin is wet. How to use it is by applying it evenly to the skin of the body and then rubbing it slowly. Body scrub components, which consist of fat components, can increase skin moisture. The water phase can increase hydration for fresh-looking skin. Surfactants in body scrubs can also replace the role of soap. One form of body scrub dosage form that is widely available on the market is the cream dosage form (Paradila et al., 2022). The caffeine content in coffee can make the skin moist so it feels smoother and firmer. Arabica coffee beans contain antioxidants which can provide benefits, one of which is preventing cell damage due to exposure to free radicals. Arabica coffee with a concentration of 2% shows a good exfoliating agent that does not irritate the skin and improves the appearance of the skin without side effects (Putri et al., 2021). This study aims to formulate and evaluate the physical quality results of coffee powder body scrub cream with emulgator concentrations of 15%, 14% and 13% stearic acid, and 1%, 2% and 3% triethanolamine. Experimental research method to determine variations in the concentration of stearic acid and triethanolamine emulsifiers. Observation of the results of evaluating the physical quality of the preparation includes organoleptic tests, homogeneity, pH, stickiness tests, spreadability tests and emulsion type. The results of this research indicate that there is an influence of differences in the concentration of stearic acid and triethanolamine in that F1 has a denser form than F2 and F3, after storage for 3 weeks F2 and F3 experienced a color change to light brown. This shows that the formulation has the best properties for body scrub cream preparations, is stable and meets the requirements based on organoleptic tests, homogeneity tests, pH tests in accordance with the standard facial skin pH in general, namely 4.5-7, while for the emulsion type test, and the stability test that was carried out on day 12 did not experience any changes or phase separation, namely F1 with a stearic acid concentration of 15% and triethanolamine 1%.